Ocular Sequelae of Stevens–Johnson Syndrome: A Comprehensive Approach. (November 2020) - Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Shweta
Abstract : Abstract: The chronic sequelae of Stevens–Johnson syndrome cause severe ocular morbidity. Among the various manifestations, including dry eye, cicatrization causing forniceal shortening, adnexal disorders, lid margin keratinization, and limbal stem cell deficiency, keratinization of the lid margin leads to progressive ocular surface damage through constant blink-induced microtrauma. This damage induces corneal punctate keratopathy and neovascularization and can produce epithelial defects leading to corneal infection or perforation. Management strategies for chronic ocular sequelae are broadly categorized into ocular surface stabilization procedures, tectonic procedures, and visual rehabilitation procedures. Interventions in the acute stage of the disease include amniotic membrane grafting. Timely intervention helps to prevent deterioration of the ocular surface in these eyes.